Survival prognostic factors for differentiated thyroid cancer patients with pulmonary metastases: A systematic review and meta-analysis - Zhao, Hao; Liu, Chun-Hao; Cao, Yue; Zhang, Li-Yang; Zhao, Ya; Liu, Yue-Wu; Liu, Hong-Feng; Lin, Yan-Song; Li, Xiao-Yi (Frontiers in Oncology, 2022)
Background The prognostic factors for differentiated thyroid cancer (DTC) patients with pulmonary metastases (PM) remain scantly identified and analyzed. Therefore, this systematic review and meta-analysis were performed to identify and summarize the prognostic factors in adult DTC patients with PM to help distinguish patients with different prognoses and inform the rational treatment regimens. Method We performed a comprehensive search of the relevant studies published in the Cochrane Library, PubMed, Scopus, Embase, Wanfang database, VIP database, China National Knowledge Infrastructure, and Google Scholar from their inception until February 2021. The pooled hazard ratios (HR) for overall survival and/or progression-free survival (PFS) with 95% confidence intervals were applied to evaluate and identify the potential prognostic factors. Pooled OS at different time points were also calculated for the available data. A random-effects model was used in the meta-analysis. Results The review and meta-analysis included 21 studies comprising 2722 DTC patients with PM. The prognostic factors for poor OS were: age over 40 years (HR=7.21, 95% confidence interval [CI] 1.52-34.10, P=0.01, N=788), age over 45 years (HR=2.18, 95% CI 1.26-3.77, P<0.01, N=601), male gender (HR=1.01, 95% CI 1.01-1.19, P=0.03, N=1396), follicular subtype of thyroid cancer (HR=1.63, 95% CI 1.36-1.96, P<0.01, N=2110), iodine non-avidity (HR=3.10, 95% CI 1.79-5.37, P<0.01, N=646), and metastases to other organs (HR=3.18, 95% CI 2.43-4.16, P<0.01, N=1713). Factors associated with poor PFS included age over 45 years (HR=3.85, 95% CI 1.29-11.47, P<0.01, N=306), male gender (HR=1.36, 95% CI 1.06-1.75, P=0.02, N=546), iodine non-avidity (HR=2.93, 95% CI 2.18-3.95, P<0.01, N=395), pulmonary metastatic nodule size over 10mm (HR=2.56, 95% CI 2.02-3.24, P<0.01, N=513), and extra-thyroidal invasion (HR=2.05, 95% CI 1.15-3.67, P=0.02, N=271). The pooled 1, 3, 5, 10, 15, and 20-years OS were 95.24%, 88.46%, 78.36%, 64.86%, 56.57%, and 51.03%, respectively. Conclusions This review and meta-analysis identified the prognostic factors of DTC patients with PM. Notably, FTC, metastases to other organs, and iodine non-avidity were particularly associated with poor prognosis. The identified prognostic factors will help guide the clinical management of DTC patients with PM. Systematic review registration https://inplasy.com/inplasy-2022-2-0026/, identifier (INPLASY202220026).